Efektivitas model blended learning terhadap motivasi dan tingkat pemahaman mahasiswa mata kuliah algoritma dan pemrograman - Sarah Bibi; Handaru Jati (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2015)
Penelitian ini bertujuan untuk (1) mengetahui perbedaan motivasi dan tingkat pemahaman mahasiswa antara pembelajaran model blended learning dengan pembelajaran konvensional, dan (2) mengetahui peningkatan motivasi dan tingkat pemahaman mahasiswa akibat penerapan pembelajaran model blended learning. Jenis penelitian ini adalah quasi experimental. Populasi penelitian adalah mahasiswa semester 2 tahun ajaran 2013/2014 Program Studi Pendidikan Teknologi Informasi dan Komputer STKIP PGRI Pontianak yang berjumlah sebanyak 270 mahasiswa. Penentuan sampel menggunakan teknik purposive sampling berjumlah 156 mahasiswa. Pengumpulan data menggunakan tes soal berbentuk pilihan ganda dan angket, teknik analisis data yang digunakan adalah statistik parametrik uji-t dengan taraf signifikansi 0,05. Hasil penelitian ini menunjukkan bahwa (1) terdapat perbedaan motivasi belajar mahasiswa antara pembelajaran model blended learning dengan pembelajaran konvensional sebesar 5,782 dan terdapat perbedaan tingkat pemahaman sebesar 9,935 serta (2) ada peningkatan motivasi belajar mahasiswa akibat penerapan pembelajaran model blended learning rata-rata peningkatan 11,705 dan ada peningkatan pemahaman mahasiswa rata-rata peningkatan 30,288. THE EFFECTS OF BLENDED LEARNING MODEL ON THE STUDENT'S MOTIVATION AND UNDERSTANDING ON THE SUBJECT OF ALGORITHMS AND PROGRAMMINGAbstractThis research aims (1) to determine the differences in motivation and understanding level of the students between learning model of blended learning and the conventional, and (2) the improvement of students learning motivation and understanding due to the use of blended learning model .This research was a quasi-experimental. The population is the second semester students of the academic year 2013/2014 Study Program Computer and Information Technology Department of Teacher Training and Education PGRI Pontianak as many as 270 students. The selection of the sample of students was done using purposive sampling technique as many as 156 students. Collecting data using test multiple-choice and questionnaire, the data analysis techniques used were statistical parametric t-test with a significance level of 0.05. The results of the research show that (1) there is a difference in learning motivation of the students between learning model of blended learning and conventional learning of 5.782 and there is difference in the understanding level of the students of 9.935 and (2) there is an improvement in learning motivation of the students due to blended learning application with an average of 11.705 and there is an improvement in the understanding level of the student with an average of 30.288.